Application of magnetic nanomaterials in magnetic-chromatography: A review - Manouchehri, Mahshid; Seidi, Shahram; Abdullah, Fuad O. (Talanta (Oxford), 2021)
With the advent of nanotechnology and its development, there have been dramatic advances in various aspects of diverse sciences. Nanotechnology encompasses the manipulating matter to create nanometre-scale materials with prodigious features and their implementation in a vast range of applications. The topic that is the current debate in today's scientific community and the transformation origin in modern technologies. Magnetic nanomaterials belong to the group of materials mainly consisting of a magnetic component, such as iron, and a chemical functionality agent. Hitherto, several reports on these materials have been published in various sciences, including chemistry, and their applications have been discussed from different perspectives. One of the most interesting aspects of these materials is in a special type of chromatographic techniques, called "magnetic-chromatography" as well as "magneto-chromatography". The subject that has been somewhat underestimated compared to the other practical aspects of these materials. This review devotes to the recent issue and seeks to address the principles, benefits, challenges, analytical data, and potential applications of magnetic-chromatography in ions separation, size fractionation of magnetic nanoparticles, and isolation of biologically active organic molecules. Also, the new aspects and future trends of this technique are discussed. [Display omitted] •Different aspects of magnetic chromatography (MC) have been overviewed.•The effects of magnetic field on the separation efficiency of MC have been investigated.•The roles of magnetic nanoparticles in MC have been explained.•The applications of MC based on magnetic nanopartices for various analytes have been summarized.•The new developments in MC have been presented.